Using the Fossil Record to Evaluate Timetree Timescales - Marshall, Charles R. (Frontiers in Genetics, 2019)
The fossil and geologic records provide the primary data used to established absolute timescales for timetrees. For the paleontological evaluation of proposed timetree timescales, and for node-based methods for constructing timetrees, the fossil record is used to bracket divergence times. Minimum brackets (minimum ages) can be established robustly using well-dated fossils that can be reliably assigned to lineages based on positive morphological evidence. Maximum brackets are much harder to establish, largely because it is difficult to establish definitive evidence that the absence of a taxon in the fossil record is real and not just due to the incompleteness of the fossil and rock records. Five primary methods have been developed to estimate maximum age brackets, each of which is discussed. The fact that the fossilization potential of a group typically decreases the closer one approaches its time of origin increases the challenge of estimating maximum age brackets. Additional complications arise: (1) because fossil data actually bracket the time of origin of the first relevant fossilizable morphology (apomorphy), not the divergence time itself; (2) due to the phylogenetic uncertainty in the placement of fossils; (3) because of idiosyncratic temporal and geographic gaps in the rock and fossil records; and, (4) if the preservation potential of a group changed significantly during its history. In contrast, uncertainties in the absolute ages of fossils are typically relatively unimportant, even though the vast majority of fossil cannot be dated directly. These issues and relevant quantitative methods are reviewed, and their relative magnitudes assessed, which are typically a function of the age of the group and the often correlated geographic range and species richness.